Access and support for persons with disabilities (PWD) in Omani higher education - Wadair, Aslam Awlad; Thien, Lei Mee (Journal of Islamic, Social, Economics and Development, 2025)
Access and support for persons with disabilities (PWDs) in higher education constitute a critical component of inclusive education, yet challenges persist globally and within the Omani context. This study aims to examine the types of access provisions and support mechanisms available to PWDs in Omani higher education institutions, as well as to identify the challenges faced by universities in facilitating inclusion. Using a qualitative research design, data were collected through semi-structured interviews with two administrative staff members from the Student Affairs Department of an Omani university. Thematic analysis was employed to analyse the data systematically. Findings reveal that higher education institutions provide various forms of support, including administrative coordination, academic guidance, counselling, physical accessibility, technological aids, and individualized strategies tailored to students’ unique needs. Despite these measures, institutional constraints such as limited policies, insufficient resources, and inadequate staff training along with academic and social barriers, including non-adapted curricula and low awareness among faculty and peers, impede the full effectiveness of inclusive practices. The study contributes to the understanding of PWD inclusion by highlighting both practical support strategies and existing gaps in policy and implementation. The findings shows a valuable insights for policymakers, educational administrators, and practitioners seeking to strengthen inclusive practices, improve access and participation, and enhance academic and social outcomes for PWDs in Omani higher education.